The extent of the legality of international humanitarian intervention in light of the rules of international humanitarian law. - Attiya, Ahmed Hatim Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
Public security, tranquility, and achieving world peace are the most important goals upon which the United Nations and the most important goals of the international community and organizations have been. Security has been and continues to be the cause of cooperation, relations, and solidarity between countries. The existence of inclusive relations between different ethnic countries only arises through feeling The public in security, which is not achieved except through the presence of jus cogent that criminalize the attack on the internal sovereignty of a country, regardless of the size of the country in which intervention is taking place and the country that interferes or the organization, and despite the protection of the international community to protect the sovereignty of the internal states, Bear on He undertakes the task of defending minorities, the displaced and the weak in the midst of wars and armed conflicts that claim the lives of countries and individuals and the failure of many refugees, displaced persons, injured and thousands of dead, which aroused the ire of some world powers from countries and international organizations for humanitarian intervention, claiming protection Human rights and freedoms from the effects of internal conflicts and civil wars have not had a great impact on our souls by examining that humanitarian international military intervention and taking note of its circumstances and circumstances.And talk about international legitimacy of human rights in general and international humanitarian law in particular raises the issue of international intervention to protect human rights, an issue that has taken a large part of attention in light of the new world order, and despite the fact that political analyzes have been used to look at the widespread interest in the principle Humanitarian intervention to protect human rights and establish democracy as a new development on the international scene in recent times, which deserves the explorers and researchers of public international law exploration of the effects and legitimacy upon which the intervening forces are based for the purpose of human intervention and through research As for us, we will be exposed to the concept of international intervention, its justifications, doctrinal objections to its existence, and the mechanisms through which the United Nations, as the mother international organization, interferes internationally through its various organs. We also look at international intervention by regional organizations and clarify what the legal basis is Which the international community relies on in international intervention, highlighting the occurrence of this interference in recent periods, especially in countries afflicted by internal conflicts, wars over power and governance, and arbitrariness against minorities and demands for secession and independence. , And what matters each researcher interested in science and legal and general public law and international humanitarian in particular.